Social Interaction Patterns in Broken Home Family Members (A Study on the Interaction of Children as Divorce Victims with Family Members in the Ronggomulyo Family of Tuban Regency) - Tutik Sulistyowati; Luluk Dwi Kumalasari; Indah Wati Afryliani (Universitas Muhammadiyah Malang, 2020)
Broken home is a condition where a family experienced a split caused by conflicts or disputes, disagreements between married couples. From the inability of married couples in maintaining the family, most couples eventually decided to have a divorce. This condition results the children to be the victims of parental divorce. It results in depression state of the child even to the frustration that is difficult to control and regulated. This study aims to find out, and describe 1) The child interaction pattern of the divorce victims with family members in Ronggomulyo Village Tuban Regency. The method used in this research is a descriptive qualitative research method. The data were obtained from observation, interview, and documentation. The research subjects have been selected based on certain criteria using purposive sampling technique. This study uses Symbolic Interactionism theory by George Herbert Mead. The results of this study are 1) The subject understanding of divorce is painful 2) The subject understanding of parent after divorce is parent experience a change in attitude 3) The subject’s actions after the divorce is changes in behavior 4) The subject’s interaction with the family members after the divorce in this research is dissociative and associative.